-4.0x+2.7-16x=-4.6x+2.7

Simple and best practice solution for -4.0x+2.7-16x=-4.6x+2.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.0x+2.7-16x=-4.6x+2.7 equation:


Simplifying
-4.0x + 2.7 + -16x = -4.6x + 2.7

Reorder the terms:
2.7 + -4.0x + -16x = -4.6x + 2.7

Combine like terms: -4.0x + -16x = -20x
2.7 + -20x = -4.6x + 2.7

Reorder the terms:
2.7 + -20x = 2.7 + -4.6x

Add '-2.7' to each side of the equation.
2.7 + -2.7 + -20x = 2.7 + -2.7 + -4.6x

Combine like terms: 2.7 + -2.7 = 0.0
0.0 + -20x = 2.7 + -2.7 + -4.6x
-20x = 2.7 + -2.7 + -4.6x

Combine like terms: 2.7 + -2.7 = 0.0
-20x = 0.0 + -4.6x
-20x = -4.6x

Solving
-20x = -4.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.6x' to each side of the equation.
-20x + 4.6x = -4.6x + 4.6x

Combine like terms: -20x + 4.6x = -15.4x
-15.4x = -4.6x + 4.6x

Combine like terms: -4.6x + 4.6x = 0.0
-15.4x = 0.0

Divide each side by '-15.4'.
x = 0

Simplifying
x = 0

See similar equations:

| 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 | | 47.39=9g+3.92 | | 6+-4+2(6)=14 | | 2(4-8)=16 | | 39+7a=-6(-6a+8) | | 3-2m+3=1-2m+6 | | 14(27-92)=37 | | 90=(3x+6)+(7x+18) | | 7(d-2)=5(d+2)-2 | | 2x+1y=11 | | 6x-10y-2y+7x+9= |

Equations solver categories